Stock Assessment Using Length-Based Bayesian Evaluation Method for Three Small Pelagic Species in the Northwest Pacific Ocean - Shi, Yongchuang; Zhang, Xiaomin; He, Yuru; Fan, Wei; Tang, Fenghua (Frontiers in Marine Science, 2022)
Chub mackerel (Scomber japonicus), Pacific saury (Cololabis saira), and Pacific sardine (Sardinops sagax) are key economic and ecological species in the Northwest Pacific Ocean (NPO). In recent years, there have been some interannual changes in their catches due to the increasing number of fishing vessels and climate change. With the establishment of the North Pacific Fisheries Commission (NPFC) to better manage these three species, it is particularly important to develop an accurate understanding of the stock status of those fisheries resources. According to the production statistics of Chub mackerel, Pacific saury, and Pacific sardine in the NPO, the length-based Bayesian evaluation (LBB) method was adopted to conduct a stock assessment on the three fisheries in this study. Research results show that the asymptotic length of Chub mackerel in the NPO Linf is 37.54 cm, with the parameter ratios of Lc/Lc_opt = 1.10, F/M = 0.57, B/B0 = 0.65, and B/BMSY = 1.10. The asymptotic length of Pacific saury in the NPO Linf is 33.24 cm, with the ratios of Lc/Lc_opt = 1.10, F/M = 0.14, B/B0 = 0.82, and B/BMSY = 2.10. While the asymptotic length of Pacific sardine Linf is 39.33 cm, with the ratios of Lc/Lc_opt = 1.20, F/M = 0.20, B/B0 = 0.77, and B/BMSY = 2.20. At present, the three species in the NPO are in a healthy state and have not yet been overfished. Body length bin may affect the estimation of some parameters without compromising the estimation of stock status. Our study indicates that the LBB model serves as an efficient method to evaluate the fisheries resources in the NPO, especially when length frequencies are the only available data. Hopefully, the results in this study can provide technical support for the conservation and management of Chub mackerel, Pacific saury, and Pacific sardine in the NPO.